2007
DOI: 10.1515/hf.2007.056
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of wood fracture mechanisms at different humidity levels

Abstract: Differences in fracture patterns and properties at various moisture levels are experimentally and numerically evaluated and discussed. Experiments were performed on spruce, pine, oak and beech. The influence of moisture at 98%, 80%, 65% and 30% RH and the mechanisms involved were investigated for softwoods and hardwoods subjected to opening mode I fracture using in situ and ex situ real-time environmental scanning electron microscopy (ESEM). The wedge-splitting technique was employed. To quantify the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 8 publications
3
32
0
1
Order By: Relevance
“…During crack propagation, the softening behavior is reported and fiber bridging occurs behind the crack tip. Like the other mechanical properties of wood, the fracture characteristics are also influenced by moisture, that is, they tend to decrease with increasing moisture content (MC) (Pluvinage 1992;Vasic and Stanzl-Tschegg 2007;Majano-Majano et al 2012). The maximal value of the stress intensity factor (i.e., fracture toughness K Ic ) is reached at 16% MC (Liyu et al 2003) or between 7% and 13% MC (Kretschmann and Green 1996).…”
Section: Introductionmentioning
confidence: 99%
“…During crack propagation, the softening behavior is reported and fiber bridging occurs behind the crack tip. Like the other mechanical properties of wood, the fracture characteristics are also influenced by moisture, that is, they tend to decrease with increasing moisture content (MC) (Pluvinage 1992;Vasic and Stanzl-Tschegg 2007;Majano-Majano et al 2012). The maximal value of the stress intensity factor (i.e., fracture toughness K Ic ) is reached at 16% MC (Liyu et al 2003) or between 7% and 13% MC (Kretschmann and Green 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The structure-property relationships of wood was investigated by EM and ESEM ex situ and in situ (Tabarsa and Chui 2000 ;Sippola and Fr ü hmann 2002 ;Fr ü hmann et al 2003 ;M ü ller et al 2003 ;Vasic and Stanzl -Tschegg 2006 ). While optical microscopy was mainly used for ex situ observations, EM and especially ESEM are very suitable for various in situ experiments to evaluate crack propagation and reaction to load (Sippola and Fr ü hmann 2002 ;Fr ü hmann et al 2003 ;M ü ller et al 2003 ;Vasic and Stanzl -Tschegg 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…While optical microscopy was mainly used for ex situ observations, EM and especially ESEM are very suitable for various in situ experiments to evaluate crack propagation and reaction to load (Sippola and Fr ü hmann 2002 ;Fr ü hmann et al 2003 ;M ü ller et al 2003 ;Vasic and Stanzl -Tschegg 2006 ). Both methods have certain disadvantages for in situ tests under mechanical load: during sample preparation, defects can be induced (Jansen et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, wood is usually far more ductile across the grain (LR and LT fracture systems), but brittle along the grain (RL, RT, TL, and TR fracture systems). Results of the previous research has also showed that wood is generally tougher radially than tangentially (Atack et al 1961;Ashby et al 1985;Stanzl-Tschegg et al 1995;Reiterer et al 2002a, b;Smith and Vasic 2003;Marki et al 2005;Vasic and Stanzl-Tschegg 2007;Yoshihara and Nobusue 2007;Majano-Majano et al 2012;Ozden and Ennos 2014;Özden et al 2016). …”
Section: Introductionmentioning
confidence: 87%